Thrombospondin-4 induces prolongation of action potential duration in rat isolated ventricular myocytes - IMOTO, Keisuke (J Vet Med Sci, 2020)
Expression of thrombospondin-4 (TSP-4), a matricellular protein, is increased in the heart tissue of various cardiac disease models. In dorsal root ganglion neurons, TSP-4 inhibits L-type Ca(2+) channel (LTCC) activity. Although TSP-4 might be related to the electrophysiological properties in heart, it remains to be clarified. The present study aimed to clarify the effects of TSP-4 on action potential (AP), LTCC current (I(CaL)) and voltage-dependent K(+) (Kv) channel current (I(Kv)) in rat isolated ventricular myocytes by a patch clamp technique. Ventricular myocytes were isolated from the heart of adult male Wistar rats. The ventricular myocytes were treated with TSP-4 (5 nM) or its vehicle for 4 hr. Then, whole-cell patch clamp technique was performed to measure AP (current-clamp mode) and I(CaL) and I(Kv) (voltage-clamp mode). The mRNA expression of Kv channels was examined by reverse transcription-polymerase chain reaction. TSP-4 had no effect on the resting membrane potential and peak amplitude of AP. On the other hand, TSP-4 significantly prolonged AP duration (APD) at 50% and 90% repolarization. TSP-4 significantly inhibited the peak amplitudes of I(CaL) and I(Kv). TSP-4 had no effect on mRNA expression of Kv channels (Kcna4, Kcna5, Kcnb1, Kcnd2 and Kcnd3). The present study for the first time demonstrated that TSP-4 prolongs APD in rat ventricular myocytes, which is possibly mediated through the suppression of Kv channel activity.